1981
DOI: 10.1128/aac.19.6.1042
|View full text |Cite
|
Sign up to set email alerts
|

Plasma disappearance, urine excretion, and tissue distribution of ribavirin in rats and rhesus monkeys

Abstract: Ribavirin has been shown to have broad-spectrum antiviral activity. To study its tissue distribution and disappearance rate, a single dose of 10 mg/kg which contained 10 ,uCi of ['4C]ribavirin was injected intravenously into rhesus monkeys and intramuscularly into monkeys and rats. Except for peak plasma concentrations and the initial phases of the plasma disappearance and urine excretion curves, no significant difference was observed between plasma, tissue, or urine values for intramuscularly or intravenously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…The efficacy of treatment appeared to be restricted here, as in the macaque model of Bolivian hemorrhagic fever and the marmoset model of AHF, to protection against the acute, hemorrhagic phase of infection. Failure to prevent (or ameliorate) the late neurological disease probably results from the inefficiency with which ribavirin crosses the blood-brain barrier (4). As virus is isolated only occasionally from the central nervous system of humans with fatal AHF (J. I. Maiztegui, C. Rivero, S. C. Levis, A. J. de Damilano, N. J. Fernandex, and D. A. Enria, III Congreso Argentina de Microbiologia, abstr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of treatment appeared to be restricted here, as in the macaque model of Bolivian hemorrhagic fever and the marmoset model of AHF, to protection against the acute, hemorrhagic phase of infection. Failure to prevent (or ameliorate) the late neurological disease probably results from the inefficiency with which ribavirin crosses the blood-brain barrier (4). As virus is isolated only occasionally from the central nervous system of humans with fatal AHF (J. I. Maiztegui, C. Rivero, S. C. Levis, A. J. de Damilano, N. J. Fernandex, and D. A. Enria, III Congreso Argentina de Microbiologia, abstr.…”
Section: Discussionmentioning
confidence: 99%
“…Objective disease parameters were monitored twice weekly for 5 weeks and then weekly for 4 weeks. These included physical examination, body weight, viremia, virus shedding from the oropharynx, neutralizing antibodies, and hematological indices.…”
Section: Methodsmentioning
confidence: 99%
“…With multiple doses over 3 days, there appeared to be a small accumulation of ribavirin in serum at the end of each day's treatment. Sequestering and clearing of ribavirin from serum would be accomplished by the incorporation of riba-virin triphosphate into erythrocytes (3) and by renal excretion (3,6), respectively. Although we did not measure ribavirin levels in the urine, previous studies in rats have shown that ribavirin is rapidly excreted in the urine (82% is excreted in 24 h) (6).…”
Section: Methodsmentioning
confidence: 99%
“…A similar study was also conducted with rhesus monkeys after i.v. dosing of [ 14 C]ribavirin (2). However, no oral dosing studies based on […”
mentioning
confidence: 99%
“…and intramuscular (i.m.) dosing of [ 14 C]ribavirin have been studied in rats (1,2). A similar study was also conducted with rhesus monkeys after i.v.…”
mentioning
confidence: 99%